2013
DOI: 10.1111/pops.12027
|View full text |Cite
|
Sign up to set email alerts
|

History Matters: Effects of Culture‐specific Symbols on Political Attitudes and Intergroup Relations

Abstract: A theory of the historical anchoring and mobilization of political attitudes is proposed, arguing that culturespecific symbols, configured by historical charters, are an important resource in defining nationhood and legitimizing public opinion in a way that makes some political attitudes difficult to change. Five studies in New Zealand and Taiwan using diverse methods converged to show that historical events with "charter status" have an additive effect in explaining variance in political attitudes regarding b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 40 publications
(83 reference statements)
3
20
0
Order By: Relevance
“…Similar to the Identity Lens Model and in accordance with the theory of social representations of history, we propose a Representations of History Lens Model through which intergroup situations are perceived. This is in line with the historical anchoring hypothesis according to which perceived relevance of historical representations serves as an anchor for intergroup attitudes (Liu, Sibley, & Huang, ). History can be an important symbolic resource that is employed to justify or reject present sociopolitical views regarding intergroup relations (Liu & László, ; Sibley et al., ).…”
Section: The Present Studysupporting
confidence: 86%
“…Similar to the Identity Lens Model and in accordance with the theory of social representations of history, we propose a Representations of History Lens Model through which intergroup situations are perceived. This is in line with the historical anchoring hypothesis according to which perceived relevance of historical representations serves as an anchor for intergroup attitudes (Liu, Sibley, & Huang, ). History can be an important symbolic resource that is employed to justify or reject present sociopolitical views regarding intergroup relations (Liu & László, ; Sibley et al., ).…”
Section: The Present Studysupporting
confidence: 86%
“…In summary, country‐level discourses about immigration and threat are produced by a combination of factors, including mass media, political leadership, demographics, and resource struggles. These form the representational resources (Liu, Sibley, & Huang, ) that can be articulated as societal‐level threats by mass media and political leaders (Powell, ; van Dijk, ). Further, these threats can produce a societal dynamic that moderates how individual‐level predictors impact on immigration attitudes in a given society.…”
Section: Country‐level Predictors: the Moderating Role Of Perceived Tmentioning
confidence: 99%
“…They found that countries with low scores on embeddedness provided contexts that activated values to predict immigration attitudes more strongly because “in less embedded societies people are socialized and encouraged to cultivate their unique preferences and ideas and to pursue their own personal goals” (p. 280). However, it seems unlikely that values should always exert a stronger influence on attitudes in low‐embeddedness contexts; rather, it seems more logical that they should be activated as guides to behavior in societies where they have formed habitual associations with the object which is being evaluated (for possible mechanisms, see Liu, Sibley, et al, ; Claassen & McLaren ). In the present research, we argue that in some countries, immigration is a more salient topic due to societal discourses emphasized in mass media, describing concerns about immigration or threat related to immigrant groups (Claassen & McLaren ; Esses, et al, ; Ettinger & Udris, ; Powell, ; Reese, ).…”
Section: Country‐level Predictors: the Moderating Role Of Perceived Tmentioning
confidence: 99%
“…A variety of indirect evidence exists for this observation. Sibley and Liu (2014) showed that there are critical differences in the types of policies supported by the public such that support for symbolic issues that value M aori culture tends to be higher than other issues aimed at actually redressing inequality via the redistribution of resources. Other research has documented differences in the importance placed on different aspects of national character (see Sibley, Hoverd, & Liu, 2011).…”
Section: The Ideology Of Symbolic Exclusionmentioning
confidence: 99%